Vietnam Nationalist Party (1924-1954) - Xuan Lam, Dinh; Van Kham, Tran (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Vietnam Nationalist Party (1924-1954) (Nguyen Van Khanh, Springer, January 2016, ISBN: 978-981-10-0073-7) *In the 1920s, an event occurred that transformed the Vietnamese political landscape. This was the almost simultaneous establishment of three political organizations: the Vietnam Revolutionary Youth League (Việt Nam Cách mạng Thanh niên đảng-VRYL) in 1925, the New Vietnam Revolutionary Party (Tân Việt Cách mạng Đảng-NVRP) in 1927, and the Vietnam Nationalist Party (1927). The assessment and evaluation of the two former organizations followed the dominant path of Vietnamese revolutionary development, which aimed toward socialism. As for VNP, from the onset, it was not clear on which position and role it would play in the revolutionary movement from 1925 to 1930. At that time it was more difficult to assess what it might influence and how it may impact on the subsequent development of the Vietnamese revolution. Materials pertaining to the development of the VNP prior to 1945, found in the occupied territory during the resistance war against France and America produced both within and outside the country were of limited value. These are mostly primarily focused on serving egoistic political interests. Within the territory occupied by the revolutionary government after 1954, when the North was liberated, there has been no monograph which gives an in–depth account of this issue and scholarly work on the subject has chiefly been some papers published on conference proceedings or paragraphs in common historical books. That led Prof. Dr Nguyễn Văn Khánh chose VNP in the history of the Vietnamese revolution, a complex issue, as a topic for his research and teaching material in the Faculty of History, University of Social Sciences and Humanities, Vietnam National University, Hanoi. Thus, this is a daring and audacious decision. The author’s mission has to research VNP in a systematic and comprehensive way, from its origins to the establishment and development, to its political ideas and organizational structure, and finally its internal divisions and decline as a political force after the Yen Bai uprising, so as to define the role and position of this organization in the revolutionary movement from 1927 to 1930 and hereafter. He has done so by making a comprehensive survey of materials, both official and unofficial, both domestic and foreign, which include not only conventional documents but also texts from localities and hometowns of vital personalities of this organization. The challenge before him was to utilize such complex collection of documents and then compare, contrast and evaluate them based on Marxist-Leninism, Hồ Chí Minh ideology, documents of the Party and with the advice of Party leaders who gave comments on VNP such as Lê Duẩn, Trường Chinh, etc. The author has done so with great success. This work, includes 8 chapters and appendixes with 197 pages, has just been published by Springer and being listed in the Scopus database. It shows value of this work for Vietnamese study scholars. Findings are presented systematically and comprehensively, relying on official and unofficial, as well as domestic and foreign sources, including texts from localities and hometowns of vital figures in the organization. The author compares, contrasts and evaluates this complex collection of documents based on the theoretical perspectives of conflict theory, social system theory, social structuralism and functionism, dialectic materialism and Marxist theory. It is essential reading for Vietnamese and international researchers interested in Vietnam’s political context in the early twentieth century and for undergraduate and postgraduate programs in Vietnam’s history and politics.